STUDY ON HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS OF ADULT KUCHCHHI CAMELS (Camelus dromedarius) - Suthar, D N; Mistry, J N; Suthar, B N; Chaudhary, S S; Patel, P B; Patel , K B (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A study was carried out to investigate the haematological and biochemical levels of Kuchchhi Camels . All the values obtained were comparable to the previous reports except PCV , and TEC which were lower and higher eosinophil count as compared to previous reports.